STUDI VOLUME LALU LINTAS DI JALAN RAYA NAROGONG CILEUNGSI, KABUPATEN BOGOR, PERIODE AGUSTUS 2011 - Syukri, Ahmad (MAJALAH ILMIAH WIDYA, 2012)
Survey of traffic volume is one of the simplest methods to obtain traffic data in order to better understand optimalisation andefficiency so that it can minimize vehicle traffic congestion problems on the highway. The method used is based on descriptive andanalytical methods, which is done is to classify the vehicles in classes manually by counting the number of vehicles per time unitbased on class - class. The purpose of the volume of traffic surveys carried out in the classified Narogong Cullinan Road, Bogorregency during the period August, 2011, results that can be found is the degree of saturation of the highway is still in an acceptablelevel. Analysis of traffic flow at the study site is still under the limit congestion. It is suggested that to reduce the traffic density, thetype of heavy vehicles such as out of the factory operates around the study site between the hours of 10:00 pm to 3:00 am.